PEDAGOGICAL FEATURES OF THE DEVELOPMENT OF PHYSICAL ABILITIES OF YOUNG STUDENTS - Yormatov Gulomjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the works aimed at forming the skills and competencies of developing physical abilities of young students , the effectiveness of exercises are not only related to the organizational style of the pedagogical process, but also the information related to the individual characteristics of the students.